A new algebraic tool for simultaneous targeting and design of mass exchanger network - Wasiu Ajibola Oladosu, 1974-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2020)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 2020